Bright, Multi‐responsive, Sky‐Blue Platinum(II) Phosphors Based on a Tetradentate Chelating Framework. (27th June 2017) - Liu, Lijie; Wang, Xiang; Wang, Nan; Peng, Tai; Wang, Suning
Abstract: A new class of highly efficient and stable, blue‐phosphorescent Pt II complexes based on a tetradentate chelating framework has been found to exhibit highly sensitive and reversible responses to multiple external stimuli including temperature, pressure, and UV irradiation with distinct phosphorescent color switching—from blue to red or white. Intermolecular excimer formation is the main origin of this intriguing multi‐response phenomenon. Highly efficient singlet‐oxygen sensitization by the Pt II compounds yields UV‐light‐induced phosphorescence enhancement and color switching.